Optimal Frequency of Stiffened Piezolaminated Composite Plates Implementing a Hybrid Special Relativity Search and Hill Climbing Optimization Algorithm - Vahid Goodarzimehr; Umut Topal; Mehdi Bohlooly Fotovat (Journal of Applied and Computational Mechanics, 2025)
This study focuses on maximizing the fundamental frequency of stiffened piezolaminated composite plates using a novel hybrid optimization algorithm that combines the Special Relativity Search (SRS) and Hill Climbing (HC) techniques. The optimization process maximizes the fundamental frequency by adjusting the fiber orientations within the composite layers. The mathematical models, based on Classical Laminated Plate Theory (CLPT) are solved using MATLAB. The impact of various parameters, including boundary conditions, grid shapes, angles of diagonal ribs, and plate aspect ratios, on the optimized frequency results is thoroughly examined. The results demonstrate that the SRSHC algorithm outperforms the Special Relativity Search (SRS) algorithm, confirming its effectiveness in complex optimization problems with large search spaces. This research contributes to advancing the design of smart structures with enhanced dynamic performance.